Ten thousand light years from okay : a novel - Dobmeier, Tracy; Katzman, Wendy (Lake Union Publishing, 2025)
"A widowed and grieving young novelist believes her words create realities--both tragic and charmed--in a hopeful and surprising novel about family, newfound love, and moving on"--